Effects of varying establishment approaches on the growth of urban street trees. Issue 4 (2nd October 2018) - Ow, Lai Fern; Ghosh, Subhadip; Mohamed Lokman Mohd., Yusof
ABSTRACT: Limited rooting space is frequently a major impediment to the growth of street trees. Different approaches to enhance the soil volume accessible to roots have been implemented in urban cities within the last decade. This survey observed the growth and health of trees planted in a) structural, load-bearing soil; b) biochar-stone-based load-bearing soil; and c) planting pits installed with structural cells. These alternative planting methods were compared against trees grown in conventional planting pits. The experimental trees were either street trees or sited within a plantation with similar soil conditions. The results indicated that tree growth and health ratings were found to be superior in the order of, planting in pits with structural cells, load-bearing material of structural soil and the biochar-stone blend, and conventional planting pits. Tree growth in structural cells was found to be 37% higher than conventional planting pits. As such, these approaches can be considered at sites where conventional pits cannot be used for tree establishment. Tree growth in pits with structural cells is therefore recommended wherever space for large planting pits is limited and when trees need to be sited close to infrastructure.